Simulation study on the optimal shape of electrodes quadrupole electrostatic deflectors for the UTEM - He Chen; Zhongwen Li; Jun Li; Huanfang Tian; Huaixin Yang; Jianqi Li (Results in Physics)
In this paper, the electrostatic field of a quadrupole electrostatic deflector used in ultrafast transmission electron microscopy is simulated. When the electrodes of the deflector are arcs and straight plates with different degrees of curvature, there is a significant difference in the distribution of the electric field at the center. The electric field distribution results of different initial electrode models were obtained by simulation, and the ‘standard deviation of electric field strength’ was defined to assess the uniformity of the central electric field distribution. The optimal arc electrode model can be obtained by fitting the cross-sectional electric field parameters obtained from the simulation. By further simulating and calculating the particle beam trajectory of the optimized model of the quadrupole electrostatic deflector electrode, it can be verified that the image quality of the optimal model is the most ideal. Then, this paper presents the optimal circular arc electrode structure parameters for a series of installation apertures, providing a reference for electrode design in relevant instruments.